Immigration policy index1. Issue 1 (January 2017) - Vikhrov, Dmytro
Abstract: The immigration policy index is based on three types of entry visa restrictions: visa required, visa not required for short stays and visa not required. I identify country pairs which changed their visa regime during 2000–2010 and find that the weakening of visa policy is associated with a 10 percent increase in migrant stocks and a significant shift towards male and less skilled migration from policy affected source countries. In contrast, the tightening of visa policy is not related to a significant change in migrant stocks, their gender or skill composition. The result suggests the existence of immigration policy hysteresis.